Integração de um Banco de Dados e um Data Warehouse sobre um Sistema de Arquivos Paralelos - Costa Neto, José Craveiro da; Guardia, Hélio Crestana; Sato, Liria Matsumoto (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2001)
Nowadays, there is an increasing demand for data warehousing systems, which are computational systems to support decision making based on information stored in a data warehouse. In order to provide such systems with high performance, a concurrent database system, called CDBS, has been proposed, CDBS integrates parallel database and warehousing technologies, and contains a data definition and manipulation function library that makes it possible to create, modify, and search on parallel databases and warehouses. In order to guarantee high performance, CDBS uses a parallel file system, called NPFS, which organizes data in such a way that its data manipulation functions can be executed rapidly. In this paper, we describe CDBS and present a case study in which the use of parallelism in databases and warehousing systems is required in order to achieve high performance. Resides, we discuss future rescarch opportunities related to the specification, design and implementation of new CDBS library functions, as well as the main contributions of this work.